2012
DOI: 10.1155/2012/236384
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Hydrolysates fromStichopus horrensas a New Source for Angiotensin-Converting Enzyme Inhibitory Peptides

Abstract: Stichopus horrens flesh was explored as a potential source for generating peptides with angiotensin-converting enzyme (ACE) inhibitory capacity using 6 proteases, namely alcalase, flavourzyme, trypsin, papain, bromelain, and protamex. Degree of hydrolysis (DH) and peptide profiling (SDS-PAGE) of Stichopus horrens hydrolysates (SHHs) was also assessed. Alcalase hydrolysate showed the highest DH value (39.8%) followed by flavourzyme hydrolysate (32.7%). Overall, alcalase hydrolysate exhibited the highest ACE inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 42 publications
7
38
1
5
Order By: Relevance
“…The current results (pattern of protein-hydrolysis) are in accordance with previously published findings (Barbana and Boye, 2011;Forghani et al, 2012;Li et al, 2014;Segura Campos et al, 2010, 2013. The efficiency of a protease in producing ACE-inhibitory hydrolysates seems to depend on the nature of the substrate protein as well as the type of protease used for hydrolysis.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The current results (pattern of protein-hydrolysis) are in accordance with previously published findings (Barbana and Boye, 2011;Forghani et al, 2012;Li et al, 2014;Segura Campos et al, 2010, 2013. The efficiency of a protease in producing ACE-inhibitory hydrolysates seems to depend on the nature of the substrate protein as well as the type of protease used for hydrolysis.…”
Section: Resultssupporting
confidence: 93%
“…The present results demonstrate the effectiveness of papain for generating a potent ACE-inhibitory PKC protein hydrolysate and are in agreement with those obtained for yellow pea (Golden), winged bean seed and whey cheese proteins (Abubakar et al, 1998;Barbana and Boye, 2010;Yea et al, 2014). However, the present results are in contrast with those obtained for Stichopus horrens flesh protein hydrolysate, which generated an efficient ACE-inhibitory hydrolysate when alcalase was used for hydrolysis (Forghani et al, 2012). It seems that difference in amino acids chains and composition of PKC and Stichopus horrens protein is the main reason, which papain is more effective to hydrolyze the PKC protein.…”
Section: Resultssupporting
confidence: 90%
“…Thus, liver hydrolysate protein likely has large numbers of sites suitable for the enzymatic cleavage activity of Alcalase; the protein was less suitable for cleavage by Protamex and the Protamex/Alcalase combination. Our results were congruent with other studies on Atlantic cod viscera (Aspmo et al, 2005), sea cucumber (Forghani and Ebrahimpour, 2012) and red salmon heads (Sathivel et al, 2005), which demonstrated the efficacy of Alcalase in protein cleavage for producing small peptides. glutamic acid (14.6 and 17.8%, respectively), glycine (9.2 and 9.9%, respectively) and aspartic acid (8.6 and 9.9%, respectively).…”
Section: α-Glucosidase Inhibitory Activitysupporting
confidence: 93%
“…Gelatin is a soluble protein obtained by partial hydrolysis of collagen, mainly from animal skin, bone, tendon, and cartilage [50]. So far, studies on sea cucumber collagen have been mainly focused on functions of hydrolytic bioactive peptides, including damaged tissue repairing [51], antitumor [52], antioxidant [53], and angiotensin-converting enzyme inhibitory activity [54,55]. Due to their antioxidant properties, collagen fibres have been used in skin care products [56,57].…”
Section: Collagenmentioning
confidence: 99%